The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1167/iovs.61.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive Fusional Vergence and Its Plasticity Are Impaired in Convergence Insufficiency

Abstract: We compared the adaptive capacities of reflexive fusional convergence and divergence in 10 participants with untreated convergence insufficiency (CI) to 10 agematched binocularly normal controls (BNCs) in an effort to elucidate the functional basis of CI. METHODS. Vergence responses were monitored binocularly at 250 Hz using video-based infrared oculography, while single and double-step disparity stimuli were viewed dichoptically. The double-step stimuli were designed to induce an adaptive increase in the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(110 reference statements)
1
3
0
Order By: Relevance
“…Our group completed a pilot study demonstrating that young adult CI participants had significantly slower peak velocity compared to BNC 28 . Slower peak velocity in CI participants has also been observed by others in the young adult population 34 , the pediatric population 35 , concussed pediatric with CI population 36 , and mild traumatic brain injury with CI participants 37 . The novelty of this current work is that it is the first to demonstrate a correlation between vergence peak velocity and the right cuneus functional activity.…”
Section: Discussionsupporting
confidence: 62%
“…Our group completed a pilot study demonstrating that young adult CI participants had significantly slower peak velocity compared to BNC 28 . Slower peak velocity in CI participants has also been observed by others in the young adult population 34 , the pediatric population 35 , concussed pediatric with CI population 36 , and mild traumatic brain injury with CI participants 37 . The novelty of this current work is that it is the first to demonstrate a correlation between vergence peak velocity and the right cuneus functional activity.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, it was shown that the induced stress resulted in a deficit of binocular stability after only 10 minutes of exposure to images with conflicting binocular and focus cues ( Mon-Williams, Wann, & Rushton, 1993 ). Observed shifts of horizontal phorias ( Mon-Williams, Wann, & Rushton, 1993 ; Karpicka & Howarth, 2013 ) and altered near point of convergence ( Wee et al, 2012 ; Yoon et al, 2020 ) might be proposed as indicators of the increased load on the convergent fusional reserves ( Wann, Rushton, & Mon-Williams, 1995 ; Erkelens & Bobier, 2020 ). Moreover, it was demonstrated that the accuracy of spatial judgments in the stereoscopic environment correlated with convergent fusional reserves, near point of convergence, and stereoscopic acuity thresholds ( McIntire et al, 2014 ), and fusional reserves allowed the prediction of the realism of depth in stereoscopic displays ( Hibbard, Haines, & Hornsey, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to adapt the fast fusional is correlated to the ability to adapt the slow fusional vergence system in BNCs, meaning those who can exhibit larger amounts of modification or change to the fast fusional system also exhibit larger amounts of change to the slow fusional vergence system and vice versa. 23,71 The ability to adapt the fast fusional system 72,73 and the slow fusional system 40,41 is reduced in patients with CI and improves post orthoptics/vision therapy. 30,31,43,55,[74][75][76][77] Prior studies of phoria adaptation report similar trends as those reported here.…”
Section: Disparity Vergence Adaptationmentioning
confidence: 99%
“…11 , 22 , 23 Others suggest that binocular vision disorders, like CI and convergence excess, may result from underlying adaptive disorders, such as abnormal vergence or phoria adaptation. 23 32 …”
mentioning
confidence: 99%